Implementasi Kurikulum Merdeka Pada Sekolah Dasar Systematic Literature Review - Hasan, Hawa; Lesmawan, I Wayan; Suastra, I Wayan (Universitas Muhammadiyah Makassar, 2024)
This study aims to obtain data on the implementation of Merdeka Curriculum in primary schools in 2024, through a Systematic Literature Review approach. The Merdeka Curriculum is designed to create a dynamic and inclusive learning environment that fosters creativity, innovation, and independent learning, and provides more autonomy to schools and educators in the learning process. This research identifies, analyses, and synthesises various studies related to the implementation of Merdeka Curriculum in primary schools, focusing on challenges, strategies, and their impact on the learning process and student development. The results show that the implementation of Merdeka Curriculum has a significant effect on students' interest in learning and character. However, some obstacles are still faced by teachers, including understanding the concept of